Glocalization of Christian Social Responsibility: The Contested Legacy of the Lausanne Movement among Neo-Evangelicals in South Korea1 - Suh, Myung-Sahm (Religions, 2015)
This paper examines the contested legacy of the First Lausanne Congress in South Korean neo-evangelical communities. In response to growing political and social conflicts in the Global South during the 1960s and 1970s, thousands of evangelical leaders from more than 150 countries gathered at Lausanne, Switzerland, in 1974 to discuss the proper relationship between evangelism and social action. The meeting culminated with the proclamation of the Lausanne Covenant, which affirmed both evangelism and public involvement as essential elements of the Christian faith. However, the absence of practical guidelines in the Covenant opened the door for all sorts of evangelical social activism, whether from the Evangelical Right or the Evangelical Left, for years to come. In light of such diverse ramifications of the Congress at both the global and local level, this paper explores the various ways in which the idea of Christian social responsibility has been interpreted and implemented by two distinct generations of neo-evangelical social activists in contemporary South Korea in relation to their respective socio-historical experiences of the Cold War and the 1980s democratic movement.